Autosomal dominant and autosomal recessive polycystic kidney disease: hypertension and secondary cardiovascular effect in children - Lucchetti, L.; Chinali, M.; Emma, F.; Massella, L. (Frontiers in Molecular Biosciences, 2023)
Autosomal dominant (ADPKD) and autosomal recessive (ARPKD) polycystic kidney disease are the most widely known cystic kidney diseases. They are significantly different from each other in terms of genetics and clinical manifestations. Hypertension is one of the main symptoms in both diseases, but the age of onset and secondary cardiovascular complications are significantly different. Most ARPKD children are hypertensive in the first year of life and need high doses of hypertensive drugs. ADPKD patients with a very early onset of the disease (VEOADPKD) develop hypertension similarly to patients with ARPKD. Conversely, a significantly lower percentage of patients with classic forms of ADPKD develops hypertension during childhood, although probably more than originally thought. Data published in the past decades show that about 20%–30% of ADPKD children are hypertensive. Development of hypertension before 35 years of age is a known risk factor for more severe disease in adulthood. The consequences of hypertension on cardiac geometry and function are not well documented in ARPKD due to the rarity of the disease, the difficulties in collecting homogeneous data, and differences in the type of parameters evaluated in different studies. Overall, left ventricular hypertrophy (LVH) has been reported in 20%–30% of patients and does not always correlate with hypertension. Conversely, cardiac geometry and cardiac function are preserved in the vast majority of hypertensive ADPKD children, even in patients with faster decline of kidney function. This is probably related to delayed onset of hypertension in ADPKD, compared to ARPKD. Systematic screening of hypertension and monitoring secondary cardiovascular damage during childhood allows initiating and adapting antihypertensive treatment early in the course of the disease, and may limit disease burden later in adulthood.